Penerapan Metode Gamifikasi Mengguakan Kahoot untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Informatika Kelas VIII di SMPN 2 Cibingbin - Dahrudi, Rudi; Setiawan, Dena Latif (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to enhance learning motivation through the application of gamification methods using Kahoot. The research employed a quantitative approach with a pretest-posttest control group design. The sample consisted of class VIII A as the experimental group (25 students) and class VIII B as the control group (25 students). Data were collected using a learning motivation questionnaire with 15 statements administered during both the pretest and posttest. The data was analyzed using quantitative descriptive methods. The results showed an increase in learning motivation between the experimental and control groups. The average posttest score of the experimental class was 61.52, while the control class scored 46.04. The Independent Samples t-test produced a value of t = 10.101 > ttable = 2.064 with a significance level of p = 0.000 < 0.05, indicating a significant difference between the two groups. The Paired Samples Test also showed a significant difference (t = -11.222; p = 0.000) in the improvement of motivation scores between the control and experimental classes. Therefore, the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. The application of gamification using Kahoot has been proven effective in improving students’ learning motivation in Informatics subjects.